Analysis of Factors that Influence the Stunting Event in Toddlers in Public Health Center Gandusari Blitar District - Qurotul Aini; Byba Melda Suhita; Novita Ana Anggraini (Journal for Quality in Public Health, 2020)
Nutritional problems, especially stunting in infants can inhibit a child's development, with negative impacts that will take place in the next life. The purpose of this study was to analyze the influence of parenting, breastfeeding, the role of health workers on the incidence of stunting in infants at the Gandusari Public Health Center in Blitar Regency. This research design is correlational analytic with cross sectional approach. with the focus of his research directed to be analyzing some of the factors that influence the incidence of stunting in UPT Public Health Center Gandusari Blitar Regency with a population of 163 respondents and a sample of 115 respondents taken by the Simple Random Sampling technique. Data collection using a questionnaire, data analysis with logistic regression test at α = 0.05. The results showed that there was an influence of parenting on the incidence of stunting in infants (p-value = 0,000), there was an effect of breastfeeding on the incidence of stunting in infants (p-value = 0.008), there was an influence on the role of health workers on the incidence of stunting in infants (p -value = 0.003). It can be concluded that the incidence of stunting in infants at the Gandusari Community Health Center is influenced by parenting, breastfeeding, and the role of the health worker at 33% while the remaining 67% is influenced by other factors. parenting, breastfeeding, the role of health workers are factors that influence the incidence of stunting. Lack of knowledge leads to the formation of negative attitudes towards stunting prevention efforts by mothers and cadres due to lack of information.